Parking Needs in Kabupaten Blora: A Case Study of Provincial Highways - Mardiana, Tetty Sulastry (KnE Social Sciences, 2022)
Street parking is allowed in certain locations of Dinas Perumahan dan Perhubungan (Diperkimhub) Kabupaten Blora (Blora Regency), to meet parking needs; however, some vehicles also park on the street in areas with parking restrictions. Based on the need for providing parking spaces while maintaining traffic order, without reducing the level of road services, this study on the parking needs in Kabupaten Blora (Blora Regency) was carried out. This study used the space unit research method approach (SRP) to determine the supply and demand for on-street parking in Cepu District. The survey showed that the location of the on-street parking on Jalan RSU provides enough parking spaces on weekdays and holidays, with less than 50% occupancy (ranked as medium-low), while the Jalan Pasar Plaza on-street parking area cannot meet the parking space requirement and has a 14.6% parking space shortage. In order to overcome this issue on Jalan Pasar Plaza, utilizing motorcycle parking spaces, which have low occupancy rates, is necessary. The shortage of on-street parking locations only occurs at certain times with an incremental percentage. The on-street parking locations in Blora Regency also need to be updated to avoid parking violations, by installing parking signs, retribution information boards, and parking area barriers. Recommended long-term plans include to develop a parking system using metered parking and subscription parking, provide parking attendant salaries according to the minimum wage, distribute fines to vehicles that park inappropriately, limit parking spaces on the street, and build parking facilities (park and ride) in order to avoid disruptions in road use due to roadsides being used for on-street parking. Keywords: parking arrangement, on street parking, off street parking, roadside